Portraying EFL Students Individual Different in Learning English - Sugianto, Sugianto; Defitranita, Defitranita; Apriani, Eka; Syafryadin, Syafryadin (International Journal of Education Research and Development, 2021)
The objectives of this research are to find out the low and high achiever students’ individual differences in learning English . in this study, the researcher used qualitative methods study.The population and the subject of this research were consisted of three low achiever student and three high achiever student at TBI which are the total number six students. In this study, the researcher took purposive sampling and the instrument used is interview. The individual differences consisted of age, sex, aptitude, motivation, learning styles, learning strategies, personality. The data showed that the low achiever student motivation is to obtain sarjana degree, use more cognitive strategies, preffer to study with friend, choose the extrovert way in learning, use to fight with the inhibition, and having the anxiety in learning English. while the high achiever wanted to be the native like, using less cognitive strategies, preffer to study alone, use the introvert way in acquiring language, and let the inhibition win. There some similarities between both student such as they couldnt comprehend the material in relatively shortime, they plan monitor and evaluate their English, like to watch english stuff and listen to song to improved their English, they both prefer learning with the phsycally activities involved, like solving problem while learning English,  their confidence built by their experienced in learning English and the last their prefer the democratic classs than the traditional one because the same reason.